Non-muscular structures can limit the maximal joint range of motion during stretching - Nordez, A.; Gross, R.; Andrade, R.; Le Sant, G.; Freitas, S.; Ellis, R.; McNair, P. J.; Hug, F. (Sports Medicine, 2017)
Stretching is widely used in sport training and clinical practice with the aim of increasing muscle-tendon extensibility and joint range of motion. The underlying assumption is that extensibility increases as a result of increased passive tension applied to muscle-tendon units. In some stretching protocols, this condition is not always met sufficiently to trigger adaptation within the muscle-tendon unit. For example, there is experimental evidence that both acute and chronic stretching interventions may increase the maximal range of motion in the absence of changes in the passive torque-angle curve. We contend that these results are partly explained by the influence of non-muscular structures that contribute only marginally to the passive torque. The potential candidates are the nervous system and fasciae, which would play an important role in the perception of the stretch and in the limitation of the range of motion of the maximal joints. At least in part, this may explain the lack of a significant effect of some chronic stretching interventions to change passive muscle tension.